EFFECTS OF FUROSEMIDE ON URETERAL DIAMETER AND ATTENUATION USING COMPUTED TOMOGRAPHIC EXCRETORY UROGRAPHY IN NORMAL DOGS. Issue 1 (11th September 2012) - Secrest, Scott; Essman, Stephanie; Nagy, Jesse; Schultz, Loren
<x xml:space="preserve">Abstract</x> One of the limitations of computed tomographic excretory urography (CTEU) for diagnosis of ureteral disease in dogs is that normal ureteral peristalsis can cause intermittent and inconsistent filling. The aims of this study were to determine if the addition of furosemide to a standard CTEU protocol would increase identification of the ureteral segments, increase ureteral attenuation and increase ureteral diameter in normal dogs. Standard and furosemide‐enhanced CTEU scans were acquired in 14 healthy dogs 3 and 10 minutes postcontrast. Ureteral diameters, attenuation values, and percent ureteral filling scores were recorded without the knowledge of furosemide treatment. Comparisons were made between treatments for each postcontrast scan time. The addition of furosemide to the CTEU protocol improved visualization of the ureters by significantly increasing the number of ureteral segments that were able to be identified, as well as their diameter when imaging the patient 3 min following contrast injection (P = 0.012). No major side effects were observed at the dose of 4 mg/kg. There was no advantage to imaging dogs 10 min following contrast administration as the ureteral segments were less attenuating and a smaller percentage of the ureter could be identified. We conclude that the addition of furosemide to canine CTEU studies is safe and may help improve visualization of the ureters.